2000
DOI: 10.1128/aem.66.4.1634-1638.2000
|View full text |Cite
|
Sign up to set email alerts
|

Nitrile Hydratase and Amidase from Rhodococcus rhodochrous Hydrolyze Acrylic Fibers and Granular Polyacrylonitriles

Abstract: Rhodococcus rhodochrous NCIMB 11216 produced nitrile hydratase (320 nkat mg of protein ؊1) and amidase activity (38.4 nkat mg of protein ؊1 ) when grown on a medium containing propionitrile. These enzymes were able to hydrolyze nitrile groups of both granular polyacrylonitriles (PAN) and acrylic fibers. Nitrile groups of PAN40 (molecular mass, 40 kDa) and PAN190 (molecular mass, 190 kDa) were converted into the corresponding carbonic acids to 1.8 and 1.0%, respectively. In contrast, surfacial nitrile groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…15,16 The recent expansion of nitrile-dependent biotransformation and enzymatic detoxification of nitrile-based herbicides and the instability of mesophilic nitrile metabolizing enzymes have led to the investigation of thermophilic bacteria as an alternative source of these activities. 17,18 We have isolated a gram positive, thin, long filamentous rod shaped thermophilic nitrilase-producing bacterium from the desert region of Rajasthan. The culture was strongly induced by benzonitrile with temperature optima in the range 45-50…”
Section: Introductionmentioning
confidence: 99%
“…15,16 The recent expansion of nitrile-dependent biotransformation and enzymatic detoxification of nitrile-based herbicides and the instability of mesophilic nitrile metabolizing enzymes have led to the investigation of thermophilic bacteria as an alternative source of these activities. 17,18 We have isolated a gram positive, thin, long filamentous rod shaped thermophilic nitrilase-producing bacterium from the desert region of Rajasthan. The culture was strongly induced by benzonitrile with temperature optima in the range 45-50…”
Section: Introductionmentioning
confidence: 99%
“…Although PANbased materials were for a long time believed to be resistant to biodegradation, it has recently been shown that a novel strain of Micrococcus luteus can degrade this material, see Figure 15.2 . Using 13 C -labeled PAN, release of polyacrylic acid was measured with NMR analysis during bacterial degradation [99,100] .…”
Section: Surface Hydrolysis Of Polyacrylonitrilesmentioning
confidence: 99%
“…The XPS signal is specific to a polymer surface, as the signals result from a combination of interactions with surfaces and layers immediately underneath (Babu et al, 2011;Tauber et al, 2000). Changes in acrylic fabric surface by nitrilase hydrolysis was analyzed with an AXIS Nova-XRF (WD) (Kratos Analytical Co., UK).…”
Section: Effects Of Commercial Nitrilase Hydrolysis On Acrylic Fabricmentioning
confidence: 99%
“…There are two different pathways for the enzymatic modification of polyacrylonitrile (acrylic) fibers: One method uses nitrile hydratases (NHase, EC 4.2.1.84; lyase), and the other uses nitrilases (EC 3.5.5.1) (Babu et al, 2011;Bornscheuer & Kazlauskas, 2005;Kobayashi & Shimizu, 2000). NHase hydrolysis involves two enzymes: NHase, which catalyzes the hydrolysis of a nitrile to an amide and amidase (EC 3.5.1.4), which sequentially converts the amide to carboxylate ions and ammonia (Battistel et al, 2001;Kobayashi & Shimizu, 2000;Tauber et al, 2000). In the other pathway, nitrilase (EC 3.5.5.1) directly hydrolyzes the nitrile to produce ammonia and the corresponding carboxylate ions on the fabric surface.…”
Section: Introductionmentioning
confidence: 99%